2011
DOI: 10.5772/50950
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Silica Nanoparticles and its Beneficial Role in Cementitious Materials

Abstract: Spherical silica nanoparticles (n-SiO2) with controllable size have been synthesized using tetraethoxysilane as starting material and ethanol as solvent by sol-gel method. Morphology and size of the particles was controlled through surfactants. Sorbitan monolaurate, sorbitain monopalmitate and sorbitain monostearate produced silica nanoparticles of varying sizes (80-150 nm), indicating the effect of chain length of the surfactant. Increase in chain length of non-ionic surfactant resulted in decreasing particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 18 publications
(15 reference statements)
5
51
0
5
Order By: Relevance
“…There are some separated cavities due to the CO 2 departure during CaO preparation from the limestone [34]. For SiO 2 as shown in Figure (5b), the particles are defined and their shapes are irregular [24]. Figure (5c) shows the SEM of the composite CaSo 4 -CaO-SiO 2 /SO 4 2-catalyst of 1:1 SiO 2 to CaO weight ratio.…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 97%
See 1 more Smart Citation
“…There are some separated cavities due to the CO 2 departure during CaO preparation from the limestone [34]. For SiO 2 as shown in Figure (5b), the particles are defined and their shapes are irregular [24]. Figure (5c) shows the SEM of the composite CaSo 4 -CaO-SiO 2 /SO 4 2-catalyst of 1:1 SiO 2 to CaO weight ratio.…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 97%
“…The bands at 674 and 597 cm -1 represents the Ca-O bonds [31,32] these bands appear stronger and sharper by increasing the CaO weight ratio. On the other hand, the IR band at 1120 is related to SiO 2 [24] that appear strongly in the high SiO 2 weight ratio. The IR peaks in the region of 380-400 cm -1 are associated with Si-O-Si bending vibration [33].…”
Section: Fourier Transforms Infrared Spectrometer (Ft-ir)mentioning
confidence: 99%
“…The addition oxide such as B2O3 [8]. add optical properties of glass, B 2 O 3 [9], and Na 2 CO 3 are mostly to reduce the melting point as well as to improve the optical or dielectric properties of the glass.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this study is to investigate the possibilities of using Alf 3 production waste, washed in ammonia solution, in cement stone specimens. Chemically treated silica gel additive was proved to reduce the amount of Ca(OH) 2 and CaCO 3 in hardened cement paste samples. Experimental research has revealed that the density in hydrated samples reduces from 2220 kg/m 3 to 2030 kg/m 3 with the increase of silica gel content from 0% to 35%.…”
Section: Introductionmentioning
confidence: 99%
“…Have done extensive work on preparation of silica nano particles ranging from few hundred nanometres to several micrometres by control hydrolysis of TEOS in ethanol. Preparation of silina nano particles and its beneficial role in cementitious material is documented in research papers [2,3] spherical silica nano particles (n-sio 2 ) with controllable size have been synthesized using tetra ethoxysilane as a starting material and ethanol as solvent by sol gel method. Increase in chain length of surfactant and solvent resulted in decreasing particle size of silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%